Canine Morbillivirus from Colombian Lineage Exhibits In Silico and In Vitro Potential to Infect Human Cells - Santiago Rendon-Marin; Carolina Quintero-Gil; Diego Guerra; Carlos Muskus; Julian Ruiz-Saenz (Pathogens, 2021)
Canine morbillivirus (CDV) is a viral agent that infects domestic dogs and a vast array of wildlife species. It belongs to the Paramyxoviridae family, genus Morbillivirus, which is shared with the Measles virus (MeV). Both viruses employ orthologous cellular receptors, SLAM in mononuclear cells and Nectin-4 in epithelial cells, to enter the cells. Although CDV and MeV hemagglutinin (H) have similar functions in viral pathogenesis and cell tropism, the potential interaction of CDV-H protein with human cellular receptors is still uncertain. Considering that CDV is classified as a multi-host pathogen, the potential risk of CDV transmission to humans has not been fully discarded. In this study, we aimed to evaluate both in silico and in vitro, whether there is a cross-species transmission potential from CDV to humans. To accomplish this, the CDV-H protein belonging to the Colombian lineage was modelled. After model validations, molecular docking and molecular dynamics simulations were carried out between Colombian CDV-H protein and canine and human cellular receptors to determine different aspects of the protein–protein interactions. Moreover, cell lines expressing orthologous cellular receptors, with both reference and wild-type CDV strains, were conducted to determine the CDV cross-species transmission potential from an in vitro model. This in silico and in vitro approach suggests the possibility that CDV interacts with ortholog human SLAM (hSLAM) and human Nectin-4 receptors to infect human cell lines, which could imply a potential cross-species transmission of CDV from dogs to humans.